Preserved and modified arc crust beneath the Kohistan-Ladakh arc in the western Himalaya-Karakoram region: evidence from ambient noise and earthquake data - Vivek Kumar (Frontiers in Earth Science, 2023)
This study uses ambient noise and earthquake waveform data recorded over ∼25 broadband seismic networks in the Himalayas, Tibet, and the Pamir-Hindu Kush to compute a 3-D shear wave velocity (Vs) model of the crust beneath the Kohistan and Ladakh arcs. The velocity model, with a lateral resolution of ∼30 km, is derived using a Bayesian hierarchical trans-dimensional inversion of fundamental mode Rayleigh wave group velocity dispersion measurements. The result shows evidence of a uniform upper and middle crust (Vs ∼ 3.5–3.6 km/s) underlain by an anomalous high-velocity layer (HVL) with Vs >4 km/s at depths exceeding 40 km beneath the Kohistan arc, consistent with laboratory-derived crustal models showing its pre-collisional structures. The thickness of the HVL is maximum (>20 km) in southern Kohistan, which exposes the mafic and ultramafic arc crust. In contrast, the Ladakh arc, which has seismic structures similar to those in southern Tibet, is characterized by significantly low velocities (Vs < 3.4 km/s) in the middle crust (20–40 km depth) and a relatively thin HVL (∼5–10 km) above a Moho depth, which mostly varies between 60 and 72 km. The contrasting velocity structure indicates that the Kohistan arc preserves a typical arc-like crust, whereas the Ladakh arc has undergone significant modifications since the India-Asia collision.